Coal mining reclamation as an environmental recovery effort: a review - Priyaji Agung Pambudi; Suyud Warno Utomo; Soemarno Witoro Soelarno; Noverita Dian Takarina (Brawijaya University, 2023)
The exploitation of natural resources remains a common practice in many countries to stimulate economic growth, and coal is the most commonly exploited resource. However, the mining process often causes environmental disturbance. Therefore, this research was conducted to analyze the ideal implementation of coal mine reclamation in Indonesia. In the post-mining area, the land is often arid, with voids that are prone to flood and erosion. The reclamation of this area is carried out by returning topsoil, adding organic material, and planting cover crops and fast-growing species. When the topographical conditions have steep slopes, scrap engineering is often added to hills up to a maximum height of 8 meters, trimming the slope with a maximum remaining slope of 35 degrees and making drainage channels with a width of more than 3 meters, a depth of more than 2 meters, and an edge slope of 2-5 percent. Approximately 70.59% of reclamation programs in Indonesia are aimed at reforesting mining areas into secondary forests because they were previously a forest ecosystem. The types of reclamation that had been carried out but were still uncommon included aquaculture, urban forests, parks playground, sports park, cattle farms, and fauna conservation ecotourism. A new approach to reclamation, such as eco-habitat, is important to obtain optimal social, economic, and ecological benefits. This approach involves optimizing sources of livelihood based on area rezoning according to the level of interference, revegetation of plants involving the community, and revitalization of sources of community livelihood, specifically environmental restoration with plant species as sources of food, nutrition, minerals, income, and non-timber forest products. Therefore, the reclamation program should be carried out through a collaborative partnership between companies, local communities, academics, technical ministries, and the media.